2009
DOI: 10.1111/j.1460-2695.2009.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effect of plastic wake on plasticity‐induced fatigue crack closure

Abstract: A B S T R A C T Fatigue crack closure is strongly influenced by the plastic wake developed because of the action of precedent cycles. It is related to the load sequence and is an additional difficulty for its determination. Finite-element method has been an alternative for the study of crack closure, commonly in constant-amplitude loading. However, such analyses are complex and computationally expensive, the length of the wake simulated being a critical parameter. In this paper, a comprehensive study of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…The opening values are low at the beginning and gradually increase, rising quickly at first and then more slowly as a stable value is reached. This is a well-known trend found by different authors [22,25,29,33,34]. The crack propagation required for stabilization, Da stab , is however dependent on load parameters.…”
Section: Horizontal Size Of Refined Mesh X Rmentioning
confidence: 75%
See 2 more Smart Citations
“…The opening values are low at the beginning and gradually increase, rising quickly at first and then more slowly as a stable value is reached. This is a well-known trend found by different authors [22,25,29,33,34]. The crack propagation required for stabilization, Da stab , is however dependent on load parameters.…”
Section: Horizontal Size Of Refined Mesh X Rmentioning
confidence: 75%
“…7. The peak was observed for plane strain state by different authors [25,33,36,51,52], while others found a stable and fast increase without initial peak [22,23,53]. Lugo et al [38] showed that the peak is not only linked to the load level, but also to the T-stress.…”
Section: Horizontal Size Of Refined Mesh X Rmentioning
confidence: 91%
See 1 more Smart Citation
“…The parameters involved in the calculation of SIF are compared in this section between fracture and fatigue simulations …”
Section: Results: Crack Front Fieldsmentioning
confidence: 99%
“…We also introduced a first three‐dimensional model with particular attention to aspects related to the study of the influence of thickness. Finally, an experimental validation was performed correlating the information obtained with the results of crack growth tests with constant amplitude loads . Since then, our objectives in numerical modelling have focused on the development of a complete three‐dimensional model of the problem.…”
Section: Introductionmentioning
confidence: 99%